Experience’s of Transtion From New Graduate Nurse (NGN) to Professional in Yemen - Muhammed Ahmed Al-Mekhlafi; Haeril Amir; Nasrullah Nasrullah; Aghata Christie Jelita Angkouw (PT.Mantaya Idea Batara, 2026)
Background: The transition from new graduate nurse to professional nurse represents a critical developmental phase marked by psychological adjustment, clinical skill acquisition, and identity formation. In fragile and resource-constrained health systems such as Yemen. This study aimed to explore the lived experiences of nurses transitioning from novice to professional roles in public hospitals in Yemen. Methods: A qualitative descriptive design was employed to obtain an in- depth understanding of participants’ experiences. Ten newly graduated nurses working in government hospitals in Yemen were recruited using purposive sampling. Data collected between January and December 2025 through semi- structured, in-depth interviews. All interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis to identify patterns and meanings across narratives. Result: Three major themes emerged. included Emotional Turbulence in Early Practice, included subthemes of transition shock, fear of clinical errors, and role uncertainty. The second theme, Developing Clinical Competence and Professional Confidence, encompassed experiential learning, mentorship support, and adaptive coping strategies. The third theme, Negotiating Professional Identity within System Constraints, comprised subthemes of interprofessional dynamics, workload pressure, and commitment to patient- centered care despite limited resources. Conclusion: Structured mentorship, supportive leadership, and competency- based transition programs are essential to facilitate smoother professional integration and enhance retention of newly graduated nurses in fragile health systems.